MODELING OF LATERAL DISTRIBUTION OF TALANGAKAR FORMATION SANDSTONE BY MULTIATTRIBUTE SEISMIC ANALYSIS IN PAGARDEWA AREA, SOUTH SUMATRA BASIN - CAHYO WIBOWO, NOOR
Pagardewa lies on Kuang High in southern part of Palembang Sub Basin, South Sumatra Basin. It is bordered by Muara Enim Deep in the western part, Lematang Deep in northern part, Garba Mountain in southern part and Kepayang Graben in eastern part. Crossplot analysis of 5 well logs data placed the gamma ray cube as model to pursue Talangakar sandstone distribution. Multi attribute seismic analysis reveals high correlation combination model, i.e. 0.712, using 4 operator and 5 attribute. Also spectral decomposition attribute mapping conducted as qualitative analysis to resolve detail sandstone distribution that has resolution below vertical seismic. Talangakar Formation is divided into 2 sequence based on sequence stratigraphic analysis. Moreover, biostratigraphy and micropaleontology data addresses first sequence as lower Early Miocene (N4-N5) deposit that decomposed in the NW-NE of Pagardewa Area. Whereas the second sequence can be identified in almost all wells in this area as upper Early Miocene (N6-N7) deposit. As the result of multi attribute and spectral decomposition analysis, the depositional model of "Bawah" Sand (first sequence) identified as fluvio-deltaic along E-W direction, which is dominated by meandering channel in the eastern to deltaic system in the western part. The second sequence of "Atas" Sand reveals the transition to innerneritic depositional system. The sedimen supply of "Atas" Sand is supposed coming from Kuang local high and Pagardewa as provenance.